Drawing Theory. An Introduction - Stefano Milani; Marc Schoonderbeek (Footprint)
Nowadays, drawing practices seem to operate in a rather uncertain field that is typical of an in-between phase of disciplinary development and that needs to be addressed, if an ‘anticipated projection’ of the development of drawing is to be attempted. The field of drawing, as practice and discourse, seems to have entered an end-condition, where the celebration of the extensive production of drawings is combined with a certain fatigue in both its understanding and reflection. Even though the role of drawing is nowadays still regarded as the most common act of architecture, this understanding of drawing is hardly subject to critical inquiries, and, unfortunately, mostly limited to its instrumental role within the representation of the project.